Transmembrane serine protease 2 (TMPRSS2) proteolytically activates the epithelial sodium channel (ENaC) by cleaving the channel's gamma-subunit - Sure, Florian; Bertog, Marko; Afonso, Sara; Diakov, Alexei; Rinke, Ralf; Madej, M. Gregor; Wittmann, Sabine; Gramberg, Thomas; Korbmacher, Christoph; Ilyaskin, Alexandr (Journal of Biological Chemistry, 2022)
The epithelial sodium channel (ENaC) is a heterotrimer consisting of alpha-, beta-, and gamma-subunits. Channel activation requires proteolytic release of inhibitory tracts from the extracellular domains of alpha-ENaC and gamma-ENaC; however, the proteases involved in the removal of the gamma-inhibitory tract remain unclear. In several epithelial tissues, ENaC is coexpressed with the transmembrane serine protease 2 (TMPRSS2). Here, we explored the effect of human TMPRSS2 on human alpha beta gamma-ENaC heterologously expressed in Xenopus laevis oocytes. We found that coexpression of TMPRSS2 stimulated ENaC-mediated whole-cell currents by approximately threefold, likely because of an increase in average channel open probability. Furthermore, TMPRSS2-dependent ENaC stimulation was not observed using a catalytically inactive TMPRSS2 mutant and was associated with fully cleaved gamma-ENaC in the intracellular and cell surface protein fractions. This stimulatory effect of TMPRSS2 on ENaC was partially preserved when inhibiting its proteolytic activity at the cell surface using aprotinin but was abolished when the gamma-inhibitory tract remained attached to its binding site following introduction of two cysteine residues (S155C-Q426C) to form a disulfide bridge. In addition, computer simulations and site-directed mutagenesis experiments indicated that TMPRSS2 can cleave gamma-ENaC at sites both proximal and distal to the gamma-inhibitory tract. This suggests a dual role of TMPRSS2 in the proteolytic release of the gamma-inhibitory tract. Finally, we demonstrated that TMPRSS2 knockdown in cultured human airway epithelial cells (H441) reduced baseline proteolytic activation of endogenously expressed ENaC. Thus, we conclude that TMPRSS2 is likely to contribute to proteolytic ENaC activation in epithelial tissues in vivo.
CRIS-Team WoS Importer:2022-06-24